Evaluation of the Use of a Diabetes Risk Test to Identify Prediabetes in an Employee Wellness Screening. (August 2022) - Ward, Eileen D.; Hopkins, Whitney A.; Shealy, Kayce
Background: The American Diabetes Association (ADA) Diabetes Risk Test (DRT) is a screening tool to identify people at risk for developing diabetes. Individuals with a DRT score of 5 or higher may have prediabetes or diabetes and should see a healthcare provider. Objective: To determine how many additional employees are identified as being at risk for developing diabetes during an employee wellness screening by using a more stringent DRT cutoff score of 4 instead of 5. Methods: During an annual employee wellness screening event, a hemoglobin A1C (A1c) was drawn for participants with a DRT score of> 4 or by request regardless of risk score. A1C values were classified as normal (<5.7%), prediabetes (>5.7 and <6.5%) or diabetes (>6.5%). Risk scores and A1C values were analyzed using descriptive statistics. Cost of additional laboratory testing was also reviewed. Results: An A1C was collected for 158 participants. Fourteen of 50 (28%) participants with a DRT of 4 had A1c values in the prediabetes range and no history of diabetes or prediabetes. Using the lower DRT score of 4 resulted in an additional expenditure of 305 with 85.40 resulting in the identification of an otherwise unaware person at risk for developing diabetes. Conclusion: Using a DRT cutoff score of 4 as part of an employee wellness screening program resulted in additional laboratory costs to identify persons at risk for developing diabetes but also allowed for earlier education to slow or stop the progression to diabetes which may reduce healthcare costs over time.